Improving scientific application execution on android mobile devices via code refactorings. (22nd June 2016) - Rodriguez, Ana; Mateos, Cristian; Zunino, Alejandro
Summary: The increasing number of mobile devices with ever‐growing capabilities makes them useful for running scientific applications. However, these applications have high computational demands, whereas mobile devices have limited capabilities when compared with non‐mobile devices. More importantly, mobile devices rely on batteries for their power supply. We initially measure the battery consumption of different versions of known micro‐benchmarks representing common programming primitives found in scientific applications. Then, we analyze the performance of such micro‐benchmarks in CPU‐intensive mobile applications. We apply good programming practices and code refactorings to reduce battery consumption of scientific mobile applications. Our results show the reduction in energy usage from applying these refactorings to three scientific applications, and we consequently propose guidelines for high‐performance computing applications. Our focus is on Android, the dominant mobile operating system. As a long‐term contribution, our results represent one more step in the progress towards hybrid distributed infrastructures comprising fixed and mobile nodes, that is, the so‐called mobile grids. Copyright © 2016 John Wiley & Sons, Ltd.